DESIGN, SYNTHESIS AND EVALUATION OF PYRAZOLE SUBSTITUTED BENZIMIDAZOLE AS AN ANTI-TUBERCULAR, ANTI-FUNGAL AND ANTI-MICROBIAL AGENT - A., VIJAY BABU; D., PRIYA; M.K., KATHIRAVAN (International Journal of Applied Pharmaceutics, 2022)
Objective: A series of pyrazole substituted benzimidazole derivatives were subjected to in silico studies to identify a new lead for anti-tubercular, antimicrobial and antifungal activity. Methods: Docking studies was carried out against Mycobacterium tuberculosis InhA bound with ETH-NAD adduct-PDB ID: 2H9I and Crystal structure of S. aureus TyrRS in complex with SB-239629-PDB ID: 1JIJ. Results: Based on the binding interactions, binding energies, and ADMET predictions, the most active compounds were produced, consisting of a para-halo phenyl substitution at the pyrazole nucleus that was connected to benzimidazole. The synthesized compounds were evaluated for tuberculostatic activity using microplate Almar blue assay method, and anti-microbial and anti-fungal activity by disc diffusion method. Conclusion: Compound 5c with chloro substituted phenyl ring on the pyrazole showed moderate anti-tubercular, mild antifungal and anti-microbial activity. This compound may thus represent a novel, multi target molecule having a selective class of anti-tubercular, anti-fungal and anti-microbial activity.